2013
DOI: 10.1111/jvh.12122
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional and dynamic change of serum metabolite profiling for Hepatitis B‐related acute‐on‐chronic liver failure by UPLC/MS

Abstract: Summary Acute-on-chronic liver failure(ACLF) is an increasingly recognized entity encompassing an acute deterioration of liver function and results in the failure of one or more organs with high short-term mortality. The focus of this study was to discover noninvasive and reliable biomarkers for the diagnosis and prognosis of hepatitis B-related ACLF. Ultra-performance liquid chromatography-mass spectrometry (UPLC/MS) was used to analyse serum metabolites of 28 patients with hepatitis B-related ACLF, 35 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 37 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…Metabolomic analysis revealed that chenodeoxycholate and glycocholic acid up-regulated the KEGG pathway of primary bile acid biosynthesis in the cecal contents of PEO group, Primary bile acids are also critical to the digestion and absorption of fat 41 . In the blood of chickens of PEO group, six lipid metabolites (such as LysoPC (18:1(9Z)) and LysoPE (16:0/0:0)) enriched fatty acid biosynthesus, Lyso PCs perform essential functions in the lipid metabolism of organisms 9,42 ; 1-Palmitoylglycerol is the biosynthetic precursor of phosphatidic acid: the major component of lysophosphatidic acid, which is a pluripotent lipid mediator which controls growth, motility, and differentiation 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomic analysis revealed that chenodeoxycholate and glycocholic acid up-regulated the KEGG pathway of primary bile acid biosynthesis in the cecal contents of PEO group, Primary bile acids are also critical to the digestion and absorption of fat 41 . In the blood of chickens of PEO group, six lipid metabolites (such as LysoPC (18:1(9Z)) and LysoPE (16:0/0:0)) enriched fatty acid biosynthesus, Lyso PCs perform essential functions in the lipid metabolism of organisms 9,42 ; 1-Palmitoylglycerol is the biosynthetic precursor of phosphatidic acid: the major component of lysophosphatidic acid, which is a pluripotent lipid mediator which controls growth, motility, and differentiation 43 .…”
Section: Discussionmentioning
confidence: 99%
“…1 H NMR spectra were acquired on a Bruker 400-MHz Avance DRX spectrometer (Bruker Biospin, Germany), operating at 400. 13 MHz with a probe temperature of 300 K. One-dimensional spin echo spectra were acquired using the Carr-PurcellMeiboom-Gill (CPMG) sequence to selectively highlight the signals from low-molecular-weight metabolites by attenuating the signals from macromolecules through a T2 filter. Each plasma spectrum was acquired using 16 dummy scans and 1,024 scans, 32,000 time domain points, a spec-tral width of 20,000 ppm, a relaxation delay of 2 s, an acquisition time of 1.36 s, and a spin echo delay of 400 s. Suppression of the water peak was achieved by water irradiation during the relaxation delay.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, metabolomics, the study of low-molecular-weight metabolites of physiological relevance, has proved an important tool for studying the changes in host metabolism during the course of viral infections (13)(14)(15)(16)(17). Since the metabolic resources crucial for viral replication are provided by host cells, the detection of changes in the metabolic profile associated with the pathological condition could help with the identification of markers of prognostic and diagnostic importance as well as the development of specific treatment strategies.…”
mentioning
confidence: 99%
“…A recent study evaluating the metabolomic profile of patients with alcoholic cirrhosis admitted to the hospital with ACLF identified signals related to ACLF, compared to compensated or decompensated cirrhosis, including lactate, pyruvate, ketone bodies, glutamine, phenylalanine, tyrosine, and creatinine 78 . Metabolic profiling has been applied in patients with HBV-related ACLF and 38 characteristic serum metabolites were identified, 17 of which also demonstrated a potential prognostic role 79 . Systemic inflammatory response is an important pathophysiologic feature of ACLF, and therefore, inflammatory or immune markers have also been investigated in this condition.…”
Section: Potential Biomarkersmentioning
confidence: 99%